Provenance graph generation for intrusion detection - Jabir Shah Halith (Nanyang Technological University, 2022)
Provenance is defined as the origin or the earliest known history of a thing. In the aspect of data provenance, it defines the origin of a data and how it was created, and actions performed on the data. These data could be used for forensics and security. This project aims to capture whole system provenance to detect any intrusion. There are multiple systems to capture the provenance such as Provenance Aware Storage System(PASS), Hi-Fi, Linux Provenance Module (LPM), CamFlow. This project focuses on setting up CamFlow, a whole-system provenance capture mechanism. The data captured from various intrusion scenarios using the CamFlow system would be streamed to Flurry. Flurry is a web server based; end-to-end data pipeline connected to CamFlow to generate provenance graphs. This project shows how CamFlow, and Flurry can be integrated to analyse for any intrusion in systems.